Multilimbed membrane guanylate cyclase signaling system, evolutionary ladder - Duda, Teresa; Sharma, Rameshwar K. (Frontiers in Molecular Neuroscience, 2023)
One monumental discovery in the field of cell biology is the establishment of the membrane guanylate cyclase signal transduction system. Decoding its fundamental, molecular, biochemical, and genetic features revolutionized the processes in developing clinical therapies for diseases of endocrinology, cardio-vasculature, and sensory neurons; lastly, it has started to leave its imprints with the atmospheric carbon dioxide. It does so via its multi-limbed structure. The inter-netted limbs throughout the central, sympathetic, and parasympathetic systems perform these functions. They generate their common second messenger, cyclic GMP to affect their physiology. Our monograph describes an historical account of their sequential evolutionary development, their structural components and their mechanisms of interaction. The foundational principles were laid down by the discovery of its first limb, the ACTH modulated signaling pathway (the companion monograph). It challenged two general existing dogmas at the time. First, there was the question of the existence of a membrane guanylate cyclase independent from a soluble form that was heme-regulated. Second, the sole known cyclic AMP three-component-transduction system was modulated by GTP-binding proteins, so there was the question of whether a one-component transduction system could exclusively modulate cyclic GMP in response to the polypeptide hormone, ACTH. The present review moves past the first question and narrates that although the cyclic GMP signaling pathway is direct, it is extremely complex. Besides ACTH, there are at least five additional limbs (Figure 11). Each embodies a unique modular design to perform a specific physiological function; exemplified by ATP binding and phosphorylation, Ca2+-sensing subunits that either increase or decrease cyclic GMP synthesis, co-expression of two Ca2+ sensors, GCAP1 and S100B, and modulation by atmospheric carbon dioxide and temperature. The complexity afforded by these multiple limbs of operation enables membrane guanylate cyclase networks to perform transductions with a diverse array of functions, exemplified by the control over cardiac vasculature, sensory neurons and, endocrine regulation.